A Cost-Effective Myoelectric Prosthetic Hand. Issue 4 (October 2018) - Atique, MD Moin; Rabbani, Siddique-e
ABSTRACT: Introduction: A cost-effective myoelectric prosthetic hand for persons with wrist amputations is a need for developing countries. Instead of trying to develop manipulation of all the fingers, which would be complex, expensive, and demanding on battery power, we took an approach to make the design simple but moderately usable. Methods and Materials: Because a sizable number of tasks can be done by controlling the thumb only, we anticipate that it would be an efficient design where the user will control only the thumb using electromyographic (EMG) signals. The shape of the hand is such that it will let the user hold small objects, such as a pen. A mannequin's hand was used as the structure, and after specific modification, the necessary circuitry was set up. Surface electrodes were used to acquire the EMG signals, which were then amplified using a bioelectric amplifier specifically designed and developed for this purpose. A microcontroller-based interface detects EMG and controls the DC gear motor that moves the thumb. Results: The thumb of the developed unit responded to contraction of the arm muscles as desired. The user can control the thumb using his or her EMG signal and write holding a pen. A box-and-blocks test was conducted in which, on average, the user was able to move 6.6 blocks per minute. Conclusions: The design is moderately usable but needs some minor improvements before practical use.